STUDI LITERATUR SISTEMATIS : GAYA KEPEMIMPINAN ORANG TUA DALAM PERKEMBANGAN SOSIAL ANAK USIA DINI - Yuliana, Yuliana; Suriansyah, Ahmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The aim of this project is to methodically investigate current research findings (2020–2024) on how parental leadership styles influence young children’s social development by identifying important trends, contextual variations, and integrating research, national and international journal papers were screened and examined using the Systematic Literature Review (SLR) methodology. According to the research, children regularly benefit from authoritarian or democratic leadership styles characterized by warmth, honest communication, and child empowerment. On the other hand, poor outcomes in emotional control, empathy, and peer interaction skills are often associated with authoritarian and permissive methods. The effectiveness of parental leadership is also influenced by the child's gender, social level, and sociocultural background. The creation of more context-sensitive tools and frameworks for parenting practices and early childhood education in Indonesia is suggested by this study, which emphasizes the significance of differentiating between parental leadership and traditional parenting.